Exploring preconception health beliefs amongst adults of childbearing age in the UK: a qualitative analysis - Laura McGowan; Emer Lennon-Caughey; Cheryl Chun; Michelle C. McKinley; Jayne V. Woodside (BMC, 2020)
Abstract Background 'Preconception health' or 'pre-pregnancy health' are terms used to describe the health status of males and females prior to pregnancy. The goal of preconception health strategies is to optimise the health of future offspring via improved parental health, which may result from planned/unplanned pregnancies. Greater emphasis is being placed upon preconception health amongst research and public health, yet there is limited evidence on this topic from the perspective of UK adults. This research explored beliefs, knowledge and attitudes on preconception health amongst adults of childbearing age, drawn from the UK. Methods A descriptive qualitative focus group study was undertaken with healthy males and females of childbearing age (18-45 years) between October 2018 and July 2019. Two groups were held in a rural location (one focus group, one mini focus group) and three groups held in an urban location (two focus groups, one mini focus group), with a range of males and females, with and without children. A semi-structured topic guide was devised based on previous literature. All groups were conducted with two researchers trained in qualitative research methods. Focus groups explored understanding/prior knowledge of preconception health, beliefs and attitudes towards preconception healthcare support and personal health. Focus groups were transcribed verbatim and analysed using thematic analysis. Results Twenty-one males and females of childbearing age (aged 18 to 45 years) participated in the research. Discussions revealed a lack of comprehensive awareness of the importance of preconception health and a sense of reluctance to visit a doctor regarding the issue, favouring the internet, unless having problems conceiving. Five themes identified included: preconception education, preconception awareness, wider knowledge networks/support, optimal parental health, and attitudes/emotions towards preconception health. The roles of males regarding positive preconception care was not well understood. Conclusions This study highlighted a lack of detailed awareness surrounding the importance of preconception health per se, despite general agreement that health status should be optimal at this time. It identified a willingness to learn more about preconception health, creating an opportunity to improve preconception healthcare awareness via evidence-based education, social media campaigns, and within healthcare systems in a life course approach.